2018
DOI: 10.1186/s13104-018-3850-3
|View full text |Cite
|
Sign up to set email alerts
|

Health care seeking behaviour of mothers towards diarrheal disease of children less than 5 years in Mekelle city, North Ethiopia

Abstract: ObjectiveTo assess the health care seeking behavior of mothers on diarrheal disease of under five children and associated factors in Mekelle City, Northern Ethiopia.ResultThis study revealed that 72.5% (n = 58) of the mothers who reported their children had diarrhea had sought health care facilities. Three quarter, (75.9%) of them was seeking health in the public health care facility. Majority, 89.3% of those children who had severe diarrhea sought at health care facilities. In the multivariable analysis, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 5 publications
5
17
1
Order By: Relevance
“…In our study, male children were more likely to get healthcare for diarrhea at health facilities as compared to females. is finding agrees with previous studies conducted in Bangladesh [21], Nigeria [32], and Nepal [29], while some researchers found no significant association between seeking healthcare for diarrhea and sex of a child [19]. Mothers who had a big problem of getting medical help for their children are less likely to seek medical treatment for fever.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, male children were more likely to get healthcare for diarrhea at health facilities as compared to females. is finding agrees with previous studies conducted in Bangladesh [21], Nigeria [32], and Nepal [29], while some researchers found no significant association between seeking healthcare for diarrhea and sex of a child [19]. Mothers who had a big problem of getting medical help for their children are less likely to seek medical treatment for fever.…”
Section: Discussionsupporting
confidence: 91%
“…Prior studies also reported a similar trend [16][17][18]. However, this finding is lower than that of previous studies conducted in Addis Ababa (70.8%), Mekelle (76%), Bangladesh (75.16%), and Gambia (81.5%) [19][20][21][22]. e finding of the study also showed that healthcare seeking for fever was lower than that of a study conducted in Ghana [23].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the current study, mothers who perceived illness was sever were seven times more likely to seek medical care than those who perceive the illness is not severed. This finding is similar to a study done in Mekele city (28). This may be due to the mother's belief of illness will improve by itself and wait until their child shows another symptom.…”
Section: Discussionsupporting
confidence: 90%
“…It is suggested that mothers/caregivers with no formal education or attended only primary school were less likely to recognize severe symptoms in their sick child, are more likely to seek traditional treatment and are less likely to have financial and other resources to take the sick child to the health facility, so, they are more likely to wait diarrhea improvement by itself at home. Moreover, mothers/caregivers with no formal education may not have basic awareness about the effect of delay in seeking care for children with diarrheal illness [12,14,33]. Therefore, intervention strategies should be designed according to the literacy level of mothers/caregivers of under-five children in order to have largest effect on child health improvement programme.…”
Section: Discussionmentioning
confidence: 99%